kvant nazariyaSIning asosiy tushunchalarini oʻquv jarayonida shakllantirish usullari - Matjanov, N.S. (SCIENCE and SOCIETY, 2020)
The article provides information on the effectiveness of pedagogical technologies in teaching topics on quantum physics in educational institutions based on the formation of students’ knowledge, skills and abilities.